Antidiabetic activity of Schkuhria pinnata – Biological screening, PK analysis and mode of action - Sewnarain, Prenitha (Division of Clinical Pharmacology, 2021)
The increasing reliance on drugs from natural sources has led to the development of several drugs from traditional plants which are present in abundance in Southern Africa. With the rapid increase of incidence of type 2 diabetes in South Africa with potentially devastating effects on healthcare, the need for alternative therapeutics is a priority. In this study, Schkuhria pinnata (Lam.) Kuntze was investigated for its antidiabetic potential. Initial screening of two different solvent extracts of S. pinnata identified an aqueous extract that lowered blood glucose concentrations in a hyperglycaemic streptozotocin-induced diabetic rat. The classical bioassay approach was followed by using different solvents, drying processes and fractionation in order to produce the most active extract and attempt to isolate an active compound(s). An aqueous freeze dried extract was found to be the most active at stimulating glucose uptake activity in C2C12 and Chang cells. Fractionation of this extract in an attempt to identify the active compound yielded a novel crystalline compound 1 by NMR analysis. Screening for bioactivity of the extract and compound 1 using C2C12 muscle and Chang cells revealed that both extract and compound 1 were biologically active, however the activity of the aqueous extract was more significant overall. A butanone/pentane extract prepared for possible commercialization purposes was also shown to be active in vitro. To establish antidiabetic activity, the aqueous freeze dried extract, butanone/pentane extract and the enriched compound 1 fraction were tested in a streptozotocin (STZ) diabetic rat model showing hypoglycaemic effects for the aqueous freeze dried extract. Messenger RNA and protein studies on C2C12 muscle cells revealed that the aqueous freeze dried extract and compound 1 enhanced insulin receptor, GLUT-4, glycogen synthase, pyruvate kinase and pyruvate carboxylase expression, suggestive of an insulin mimetic mode of action, while the butanone/pentane extract enhanced adenosine monophosphate-activated kinase (AMPK) protein expression by a non-insulin dependent mechanism. A pharmacokinetic study (PK) established bioavailability of compound 1 following oral administration of the extracts, but not from the compound 1 enriched fraction. From this study, the traditional use of S. pinnata has been scientifically validated as having antidiabetic properties. In vitro and in vivo bioassays, confirmed that an aqueous freeze dried extract which was prepared as per the traditional method had the most promising antidiabetic iii activity. Compound 1 isolated from an active fraction was proven to be almost as effective as the parent extract in in vitro studies. This compound could therefore be the major active ingredient responsible for the uptake of glucose in cells and the hypoglycaemic activity in vivo. In this study, the antidiabetic activities together with the mechanism of action of S. pinnata extracts and compound 1 were elucidated. The highlight of the study was the identification of a bioactive novel chemical entity (NCE) compound 1 (identified as 2-(2-{[(2E)-4-hydroxy2-(hydroxymethyl)but-2-enoyl]oxy}-4,7-dimethyl-1,2,3,4-tetrahydronaphthalen-1-yl)prop-2- enoic acid) isolated from an active fraction of S. pinnata that was proven to be almost as effective as the parent extract in in vitro studies. This compound could therefore be the major active ingredient responsible for the uptake of glucose in cells and the hypoglycaemic activity in vivo. The cellular mechanism of action of the S. pinnata extracts and compound 1 demonstrated both insulin mimetic and non-insulin dependent mechanisms (AMPK) in C2C12 muscle cells. Further research in the form of preclinical and clinical trials need to be undertaken to make this extract or biologically active compound available as a herbal remedy or nutraceutical therapeutic for diabetes. To achieve this; safety, efficacy and mode of action studies will have to be established. The synthesis of compound 1 and/or analogues should also be investigated as an antidiabetic drug candidate.